Revision of Mathematical Principles of Natural Philosophy Based on the UCST Realism Framework - Cui, Weicheng (European Journal of Applied Sciences, 2026)
Newton’s Mathematical Principles of Natural Philosophy established the paradigmatic foundation of classical mechanics. Nevertheless, its theoretical system suffers from profound inherent defects including ontological vacancy, circular definition, action-at-a-distance, and ambiguous origin of motion, failing to provide a self-consistent realist interpretation of the physical world. While modern physics has improved predictive accuracy, it has further introduced abstract hypotheses such as spacetime curvature, carrier-free energy, vacuum fluctuation, probabilistic wave function, and nonlocal correlation, exacerbating theoretical fragmentation and ontological ambiguity. To reconstruct the realist foundation of physics and achieve a unified description of universal phenomena, this paper systematically revises Mathematical Principles of Natural Philosophy based on the realism framework of the Unified Complex System Theory (UCST). Grounded in three fundamental philosophical ontologies—the Universe, Mind, and Aether—and taking 17 axioms as the sole logical premise, this study strictly distinguishes active force from passive force, proposes generalized living entities as the basic constituent units of the world, and regards the aether as the real medium for the transmission of force, momentum and energy. A unified dynamic equation incorporating the generalized second law of motion is thereby established, unifying macroscopic celestial motion, microscopic particle motion, fluid motion, thermal motion, wave phenomena and radiation phenomena within a single self-consistent and integrated theoretical framework. This paper demonstrates that the primary cause of all motions lies in the active force autonomously generated by living entities, whereas passive force only functions to constrain, transmit and alter motion states. Complex motion patterns such as orbit, periodicity, rotation, vibration and evolution arise necessarily from the coupling of active and passive forces. No purely inanimate entities exist in the real world; macroscopic stationary objects merely represent an ideal limit where active force approaches zero. The universe maintains perpetual motion without requiring an external "First Mover", with its fundamental origin rooted in the active force inherent in all basic constituent units. Through the ontological reconstruction of traditional mechanics, thermodynamics, wave theory and cosmology, this paper accomplishes a paradigmatic transformation of physics: from descriptive to explanatory, from fragmented to universal, and from abstraction to realism. It provides a logically self-consistent and empirically verifiable unified foundation for natural philosophy and theoretical physics.